The guitar of Baixo Alentejo (Portugal) - a journey into botanical traditions - Figueira, Ana Paula; Carvalho, Luis; Figueira, Víctor; Fernandes, Francisca Maria; Nunes, Maria de Fátima (Ethnobotany Research and Applications, 2025)
In Baixo Alentejo, a historic province in southern Portugal, musical traditions are deeply intertwined with nature, particularly through a local chordophone known as the campaniça guitar, crafted from both exotic and native Portuguese woods. This distinctive guitar, commonly played at rural festivals to provide harmony and rhythm to improvised songs, represents a centuries-old tradition that connects Portuguese culture with plant resources. Although the campaniça faced a decline in popularity towards the end of the 20th century, a revivalist movement played a crucial role in ensuring its survival. More recently, cultural centers in Castro Verde and Odemira have been established to safeguard this unique musical heritage, inspiring future generations to preserve and innovate within the tradition. Keywords: campaniça guitar, Baixo Alentejo, traditional music, ethnomusicology, ethnobotanical memory.